(3fXe GdeYdheGJ GdEOGQjI aj GdefXeGJ GdeYGUQIs - (3KGHJ YHO GdQMef(B, (3EOQjSs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI ddfTQ hGdJhRjY(B,s, 2005)
(3fXQjI GdfXe, eaghe hNUGFU hCfhGY GdfXe(B- (3fXQjI GdeYdheGJ, GdeYdheGJ cehQO QFjSj ddefXeI(B- (3GdOhQ GdESJQGJjLj dfXe GdeYdheGJ(B- (3fXe GdeYdheGJ hGdEOGQI hEJNGP GdbQGQGJ (B- (3HQGeL JTZjd GdMGSH(B- (3bhGYO GdHjGfGJ heNGRf GdHjGfGJ(B- (3GdEJUGdGJ GddGSdcjI hGdTHcGJ hGdGfJQfJ(B- (3JMdjd hJUeje fXGe GdeYdheGJ(B.s
(3GdeQGLY U(B.573s
Keywords: (3GdeYdheGJ GdEOGQjIs; (3fXe GdeYdheGJ GdEOGQjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s